(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Chloramphenicol is a broad-spectrum antibiotic, which has been used for treatment of animals. However, in humans it leads to hematoxic side effects particularly aplastic anaemia for which a dosage-effect relationship has not yet been established. The objective of this study was to validate a developed chloramphenicol enzyme linked immunosorbent assay for the determination of chloramphenicol residues in ovine tissues. Two groups (n=5) of sheep were injected with chloramphenicol sodium succinate at 25-mg/kg bodyweight and slaughtered one and four weeks post drug administration. Overall, the mean percentage recoveries in muscle, liver and kidney were 92 %, 70% and 78% respectively. The limits of detection were 1.2 ng/g, 0.6 ng/g and 0.8 ng/g while the detection capability was 2.5 ng/g, 1 ng/g and 1 ng/g in muscle, kidney and liver respectively. This enables the method to be used effectively as a screening tool for chloramphenicol residues in livestock products especially in the liver, muscle and kidney.